A review and inventory of U.S. hydrogen emissions for production, distribution and storage - Duroha, Jesse C.; Malmquist, Kenny; Vad, Nicolas; Dilsaver, Patrick; Malotte, Clarice; Matthews, Heather; Ordonez, Diana; Lariviere, Niklas; Harrison, Matt; Marchese, Anthony J. (Frontiers in Energy Research, 2025)
In response to the growing global interest in hydrogen as an energy carrier, this study provides the first attempt to develop a baseline inventory of U.S. hydrogen emissions from production, distribution and storage. The scope of this study was limited to pure hydrogen emissions and excludes emissions from low purity hydrogen streams and carriers. A detailed literature search was conducted, utilizing various greenhouse gas emissions inventory protocol principles and guidelines, to consolidate a list of activity data and emission factors. The best available activity data and emission factors were then selected, via a Multi-Criteria-Based Decision Making Method named Technique for Order Preference by Similarity to Ideal Solution, or modelled using best-engineering estimates. The study estimated total U.S. hydrogen emissions of 0.063 MMTA with emission bounds ranging from 0.02 to 0.11 MMTA. Given the total estimated H2 production capacity of 7.97 MMTA, the study estimates a total U.S. hydrogen emission rate for production, distribution and storage of 0.79% (0.26%–1.32%). To reduce the uncertainty in the estimated total hydrogen emissions, future work should be conducted to measure facility-level hydrogen emission factors across multiple sectors. The inventory framework developed in this study can serve as a living document that can be updated and enhanced as more empirical data is obtained. This study also provides detailed insights regarding key emission or leakage sources and causes from each supply chain stage. The insights and conclusions from this study can provide direction for hydrogen production companies and safety professionals as they develop hydrogen emission mitigation measures, and controls.